Marfan Syndrome beyond Aortic Root—Phenotyping Using Cardiovascular Magnetic Resonance Imaging and Clinical Implications - Evangelia Nyktari; Maria Drakopoulou; Panagiotis Rozos; Sofia Loukopoulou; Thomas Vrachliotis; Soultana Kourtidou; Konstantinos Toutouzas (Medicina, 2023)
Marfan syndrome (MFS) is an inherited autosomal-dominant connective tissue disorder with multiorgan involvement including musculoskeletal, respiratory, cardiovascular, ocular, and skin manifestations. Life expectancy in patients with MFS is primarily determined by the degree of cardiovascular involvement. Aortic disease is the major cardiovascular manifestation of MFS. However, non-aortic cardiac diseases, such as impaired myocardial function and arrhythmia, have been increasingly acknowledged as additional causes of morbidity and mortality. We present two cases demonstrating the phenotypical variation in patients with MFS and how CMR (Cardiovascular Magnetic Resonance) could serve as a “one stop shop” to retrieveS all the necessary information regarding aortic/vascular pathology as well as any potential underlying arrhythmogenic substrate or cardiomyopathic process.